Healthcare Experience of Pediatric Patients with Autism Spectrum Disorders in Saudi Arabia: A Cross-Sectional Study - Basma Al-Jabri; Sara Alnuwaiser; Haifa Abdulghaffar; Rahaf Almuhanna; Shaimaa Salaam; Raval Brika; Alia Addas; Hala Bedaiwi (MDPI AG, 2023)
Children with autism spectrum disorder (ASD) face several challenges in the healthcare setting. This study defines the challenges experienced by children with autism in hospitals in Saudi Arabia. A cross-sectional study was conducted using a questionnaire for guardians of autistic children in outpatient clinics, autism support groups, and rehabilitation centers. A total of 199 participants were included. The medical procedures causing the most anxiety to children were injections and getting their blood drawn (68.3%), vital sign measurement (41.6%), and height and weight measurement (37.8%). Long waiting hours (44.1%), increased sensory stimuli (33.2%), and overcrowding of hospital staff (27.9%) were stress-inducing in the healthcare environment. The guardians recommended that loud noises (44.7%), crowdedness (41.2%), and long waiting hours (42.1%) be avoided. The nonverbal children experienced significantly higher levels (p < 0.001) of agitation, irritability, and outbursts during doctor visits than their verbal counterparts. The children with intellectual disabilities were more tense and unresponsive during doctor visits (33.3%) than their intellectually able counterparts, who more frequently were calm and responsive (44.9%) during visits. Most patients with ASD face hardships during hospital visits. Nonverbal patients and those with intellectual disabilities have a higher tendency for hospital setting anxiety-induced outbursts, which may be eased by avoiding loud noise and overcrowding.